The Impact of Highly-skilled ICT Labour on Firm Performance: Empirical Evidence from Six European Countries - Eva Hagsten; Anna Sabadash (European Commission, Joint Research Centre (JRC), 2014)
While unemployment in the EU is above 10%, the job vacancy rate also remains high around 1.5%. This suggests considerable unmet demand for skills, which is in the focus of the EU employment promotion policies. This paper studies the special role that schooled ICT experts in firms - an intangible input often neglected and difficult to measure – play for productivity. The effects are investigated both in isolation and in conjunction with the impact of ICT maturity on microdata in six European countries (UK, France, Sweden, Norway, Denmark and Finland) for the period 2001-2009. We find that increases in the proportion of ICT-intensive human capital boosts productivity. This seems to confirm the case in favour of recruitment of highly skilled ICT employees. However, the gains vary across countries and industries, suggesting that the channels through which the effects operate are narrower for ICT-intensive human capital than for skilled human capital in general. Our findings provide an important message to the EU employment policy debate that currently revolves around the skill mismatch in general and the unmet demand for ICT skills in particular.
Keywords: J24; 330; Employment; productivity; ICT skills